Stability Of Wax-Based Oleogel As Novel Frying Medium Of Par-Fried French Fries - Lam, Xue Yuan (Universiti Sains Malaysia, 2020)
Wax-based oleogels form three-dimensional hydrophobic gel network in oil and potential to coat the surface structure of fried food from excessive oil absorption. French fries are one of the highly consumed snacks that contribute to significant fat intake around the world. Therefore, strategies to improve oxidative stability of fried food is an important aspect to be considered. The aims of this study were to investigate the functionality of wax-based oleogels as par frying medium in improving oxidative stability of fried potato strips and evaluate their effects on physiochemical properties of both frying oil subjected to repeated frying cycles and French fries. Potato strips were blanched and subjected to two-steps frying process: 1) par frying for 1 min at 190 °C without (control) and with gelled oil (0.05% wax; candelilla (CDW) or rice brand (RBW)), blast frozen at -18 °C for 30 min, and stored in freezer to mimic commercial practice, and 2) frying for 1.5 min at 190 °C. A total of 30 frying cycles were carried out. Oil samples at interval of 5 frying cycles and French fries from 1st and 30th cycles were collected for quality analyses. French fries par fried with CDW oleogel oil resulted in comparable texture and total colour difference (ΔE) of French fries with the control samples. However, RBW oleogel was slightly more prone to oxidation and resulted in darker colour French fries. For the quality of oil subjected to repeated frying cycles, the oil used to fry the CDW sample showed higher oxidative stability compared to RBW and control samples with lowest FFA value and comparable in PV and TOTOX values.